2014
DOI: 10.1631/jzus.b1300175
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial and fungal community successions under the stress of chlorpyrifos application and molecular characterization of chlorpyrifos-degrading isolates using ERIC-PCR

Abstract: Abstract:Chlorpyrifos is a widely used insecticide in recent years, and it will produce adverse effects on soil when applied on crops or mixed with soil. In this study, nested polymerase chain reaction (PCR) and denaturing gradient gel electrophoresis (DGGE) were combined to explore the bacterial and fungal community successions in soil treated with 5 and 20 mg/kg of chlorpyrifos. Furthermore, isolates capable of efficiently decomposing chlorpyrifos were molecular-typed using enterobacterial repetitive interge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…Digrak and Kazanici [2001] observed that the treatments of organophosphorus insecticides: isofenphos, phorate and fonofos had no side-effect on the development of the number of actinomycetes and fungi. Chen et al [2014)] reported the inhibitory effect of chlorpyrifos on the population of soil microorganism. Similar impact was observed for cypermthrin [Ahmed and Ahmad, 2006] and endosulfan [Nasim et al 2005].…”
Section: Resultsmentioning
confidence: 99%
“…Digrak and Kazanici [2001] observed that the treatments of organophosphorus insecticides: isofenphos, phorate and fonofos had no side-effect on the development of the number of actinomycetes and fungi. Chen et al [2014)] reported the inhibitory effect of chlorpyrifos on the population of soil microorganism. Similar impact was observed for cypermthrin [Ahmed and Ahmad, 2006] and endosulfan [Nasim et al 2005].…”
Section: Resultsmentioning
confidence: 99%
“…The same result could be concluded in this paper. Other studies have shown that this may be due to the high tolerance and adaption of some microbes in situ to chlorpyrifos (Fang et al, 2009;Chen et al, 2014). There were 5 dominant bands (a, n, o, u, x) sequenced.…”
Section: Discussionmentioning
confidence: 91%
“…The impacts of these pesticides on plant growth parameters were also monitored because these parameters are related to plant health, thereby directly influencing agricultural productivity. Limited studies [28,29] have shown the influence of pesticides on the structure of the rhizospheric microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…They were compared with azadirachtin (a biopesticide) to assess the disturbance they cause in the soil ecosystem. Both chlorpyrifos and cypermethrin have been shown to inhibit microbial growth either by a cultivation-dependent approach [16] or by qualitative analysis [13]. However, in-depth analysis of such effects has not been attempted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation